The effect of recording interval length on behavioral assessment using the forced swimming test - Paloma Álvarez-Suárez (Revista Iberoamericana de Psicología y Salud, 2015)
The forced swimming test is a method used in the assessment of depressive-like behavior in rodents. Changes in the original forced swimming test procedure developed by Por- solt et al. and their influence in the results is a controversial issue and has been discussed in many studies. Animal’s behavior is usually recorded by partial interval recording, dividing the total recording time into equal intervals and manually recording the predominant behavior. Despite the influence of the recording method in the subsequent results, this issue has not been further studied nor normalized. The aim of this study was to assess whether the repre- sentativeness of the data is influenced by the recording interval length, by recording behaviors (immobility, swim and climbing) in the same subjects at 3, 5 and 10 s recording intervals. We used a non-pathological sample of male and female adult Wistar rats. Our results show no dif- ferences in the use of these three recording intervals in the registration method of the forced swimming test, for the main three behaviors measured